Outcomes of infants with pulmonary atresia with intact ventricular septum listed for heart transplantation: A multi‐institutional study. (29th June 2022) - Joong, Anna; Zuckerman, Warren A.; Koehl, Devin; Cantor, Ryan; Alejos, Juan C.; Ameduri, Rebecca K.; Boyle, Gerard J.; Rothkopf, Amy C.; Kirklin, James K.; Gajarski, Robert J.
Abstract: Background: Management of infants with pulmonary atresia/intact ventricular septum (PA/IVS) is variable. Because of higher mortality in more severe forms, heart transplant (HT) is an acceptable approach, but waitlist and post‐transplant outcomes are unclear. This study compared outcomes of infants with PA/IVS vs. other single ventricle (SV) anatomies listed for HT. Methods: Data from the Pediatric Heart Transplant Society (1993–2018) were analyzed for survival and risk factors for mortality. Results: Of 1617 SV infants, 300 had PA/IVS (19%) and 1317 had other SV (81%). Overall, 1‐, 5‐, and 10‐year survival was higher among PA/IVS (74%, 65%, 61%) versus other SV infants (62%, 54%, 50%, p = .004). While waitlist mortality was similar between groups ( p = .09), PA/IVS was an independent predictor of improved waitlist survival (HR 0.68, p = .03), and PA/IVS infants had higher incidence of waitlist removal (8% vs. 5.5%, p = .03), most commonly for being "too well." Post‐transplant survival was superior among PA/IVS versus other SV infants (1‐ and 5‐year survival 93% and 81% vs. 80% and 71%, p < .0001). Risk factors for PA/IVS waitlist mortality (2008–2018) included extracorporeal membrane oxygenation and mechanical ventilation. Prior aortopulmonary (AP) shunt among PA/IVS infants was associated with improved waitlist survival. Conclusions: Overall survival among PA/IVS infants listed for HT exceeds that of other SV infants with PA/IVS identified as an independent predictor of improved waitlist and post‐transplant survival. Prior AP shunt among listed PA/IVS infants was associated with improved waitlist outcomes, though, which may reflect a listing selection bias.